Effects of Bi substitution on the structures, electrical properties, and transparency of Sr2Na1−3xBixNb5O15 ceramics. (April 2020) - Xu, Shudong; Yang, Pei; Deng, Zhuo; Wei, Lingling; Yang, Zupei
Graphical abstract: Highlights: Pure Sr2 Na1-3 x Bi x Nb5 O15 phase were successfully obtained after introduction of high-charge Bi 3+ . The composition with x = 0.04 exhibited optimized electrical properties and transparency. Higher densification and stronger structural distortion of the NbO6 polar contributed to the optimized performances. Abstract: Sr2 Na1−3 x Bi x Nb5 O15 ceramics (SNBN; x = 0.00, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, and 0.08) were synthesized by a conventional solid-state reaction method. To eliminate the impurity phase in the Sr2 NaNb5 O15 ceramics, we introduced high-charge Bi 3+ into the SNN ceramics to reduce the filling degree of A1 and A2 sites. X-ray diffraction results confirmed this compositional design, because all SNBN ceramics showed a pure tetragonal tungsten-bronze phase along with shrinkage of the unit cell when x > 0.01. Meanwhile, Bi 3+ introduction improved their dielectric, ferroelectric, and transparent properties. As suggested by Raman and SEM, both the higher densification with relatively uniform grain size and more distorting degree of the NbO6 polar unit contributed to the enhanced electrical properties and transparency at x = 0.04.